Analyses of firn gas samples from Dronning Maud Land, Antarctica: Study of nonmethane hydrocarbons and methyl chloride - Kaspers, Karsten Adrian; van de Wal, Roderick S. W.; de Gouw, Joost; Hofstede, Coen; van den Broeke, Michiel Roland; van der Veen, Carina; Neubert, Rolf; Meijer, Harro A. J.; Brenninkmeijer, Carl; Karlöf, Lars; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2004)
Firn air was sampled on the Antarctic plateau in Dronning Maud Land (DML), during the Norwegian Antarctic Research Expedition (NARE) 2000/2001. In this paper, we describe the analyses for methyl chloride and nonmethane hydrocarbons (NMHCs) in these firn air samples. For the first time, the NMHCs ethane, propane, and acetylene have been measured in Antarctic firn air, and concentration profiles for these gases have been derived. A one-dimensional numerical firn air diffusion model was used to interpret the measured profiles and to derive atmospheric concentrations as a function of time. The atmospheric trends we derived for the NMHC and methyl chloride at DML cover the period from 1975 to 2000. Methyl chloride shows a decreasing trend of 1.2 ± 0.6 ppt per year (annual mean concentration 548 ± 32 ppt). For ethane we found an increasing trend of 1.6 ± 0.6 ppt per year (annual mean concentration 241 ± 12 ppt). The concentrations of propane and acetylene appear to be constant over the period 1975–2000, with annual mean concentrations of 30 ± 4 ppt for propane and 24 ± 2 ppt for acetylene.
Keywords: Dronning Maud Land; NARE 2000/01; atmosfæren; gasskonsentrasjoner; geofysikk

Seasonal cycles of nonmethane hydrocarbons and methyl chloride, as derived from firn air from Dronning Maud Land, Antarctica - Kaspers, Karsten Adrian; van de Wal, Roderick S W; de Gouw, Joost; Hofstede, Coen; van den Broeke, Michiel; Reijmer, Carleen; van der Veen, Carina; Neubert, Rolf; Meijer, Harro A J; Brenninkmeijer, Carl; Karlöf, Lars; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2004)
This paper presents atmospheric concentrations of ethane, propane, acetylene, and methyl chloride, inferred from firn air by using a numerical one-dimensional firn diffusion model. The firn air was collected on the Antarctic plateau in Dronning Maud Land during the Norwegian Antarctic Research Expedition (NARE) 2000/2001. The influences of seasonal variations in temperature and pressure and the variation in accumulation rate were studied and are not negligible, but appear to cancel each other out if all variability is taken into account. This paper also demonstrates that firn air from the uppermost firn layer (30 m) can be used to derive seasonal cycles of these trace gases, without needing a year-round facility. These cycles display higher atmospheric mixing ratios during the Antarctic winter and lower atmospheric mixing ratios in summer. The cycles for the year 2000 show amplitudes of 140 ± 25 ppt for ethane, 30 ± 10 ppt for propane, 24 ± 6 ppt for acetylene, and 40 ± 20 ppt for methyl chloride. For ethane and propane the amplitudes and months of maximum atmospheric concentration (phase) are in reasonable agreement with year-round measurements at the South Pole and Baring Head (New Zealand). The amplitudes for methyl chloride and acetylene are significantly greater than seen in year-round measurements at the South Pole and at Neumayer (Antarctica), although the phase is in line. While biomass burning and removal by OH radicals can partially explain these large amplitudes, the exact cause still remains unclear for methyl chloride and acetylene.
Keywords: Dronning Maud Land; NARE 2000/01; atmosfæren; gasskonsentrasjoner; geofysikk; meteorologi

State-dependent parental care in the Antarctic petrel: responses to manipulated chick age during early chick rearing - Varpe, Øystein; Tveraa, Torkild; Folstad, Ivar (Oikos, 2004)
Life histories are state-dependent, and an individual's reproductive decisions are determined by its available resources and the needs of its offspring. Here we test how a chick's needs for food and protection influence parental decisions in the Antarctic petrel, Thalassoica antarctica, where the parents, due to their long breeding lifespan, are expected to give priority to their own needs before those of the young. We exchanged one-day-old chicks with four-day-old chicks and studied how the parents subsequently provided care to the chick. The duration of the guarding period was adjusted, and parents left older chicks earlier and younger chicks later compared to controls. Three mechanisms were responsible for the adjustments. 1) Parents with an older chick co-ordinated fewer guarding spells whereas parents with a younger chick co-ordinated more guarding spells. 2) At the last guarding spell, i.e. where a parent left the chick alone before the partner returned, less time was spent with older chicks, and more time with younger chicks. 3) Foraging trip duration was shortened by parents given older chicks and prolonged by parents given younger chicks, probably in response to the chick's food demand. Hence, the parents responded quickly to the altered needs of the chick. Parents with high body mass guarded longer and were better able to co-ordinate the guarding spells compared to lighter parents. In conclusion, Antarctic petrels adjust reproductive decisions to their own, their mate's, and their chick's state, and they seem to respond to the chick's needs for both food and protection.
Keywords: Dronning Maud Land; NARE 2000/01; fugler; ornitologi; petreller; zoologi; økologi

Using First-Passage Time in the Analysis of Area-Restricted Search and Habitat Selection - Fauchald, Per; Tveraa, Torkild (Ecology, 2003)
How animals change their movement patterns in relation to the environment is a central topic in a wide area of ecology, including foraging ecology, habitat selection, and spatial population ecology. To understand the underlying behavioral mechanisms involved, there is a need for methods to measure changes in movement patterns along a pathway through the landscape. We used simulated pathways and satellite tracking of a long-ranging seabird to explore the properties of first-passage time as a measure of search effort along a path. The first-passage time is defined as the time required for an animal to cross a circle with a given radius. It is a measure of how much time an animal uses within a given area. First-passage time is scale dependent, and a plot of variance in first-passage time vs. spatial scale reveals the spatial scale at which the animal concentrates its search effort. By averaging the first-passage time on a geographical grid, it is possible to relate first-passage time to environmental variables and the search pattern of other individuals.
Publisher: Ecological Society of America
Keywords: Dronning Maud Land; NARE 2000/01; fugler; ornitologi; petreller; satellittelemetri; økologi